Top-down, bottom-up, and horizontal mortality variation in a generalist seed beetle - AMARILLO-SUÁREZ, ÁNGELA R. (Revista Colombiana de Entomología, 2010)
The study of the interacting factors that constrain resource use in organisms and promote diversity is an important task, especially in a mega diverse area, in which the increasing transformation of ecosystems modifies the interactions among organisms. among the hypotheses that explain resource use and diversity of insects are the Top down and the Bottomup hypotheses, in which experimental studies have shown tradeoffs between these factors. The influence of parasitism, host plant and competition was evaluated to determine their effect on mortality of the seed beetle Stator limbatus from populations adapted to different host plants. Mortality of eggs caused by parasitism, and mortality of larvae caused by competition was recorded for seven populations that use a single host seed, and for one population that uses two hosts. Populations that use Acacia greggii experienced the lowest mortality, and populations that use Parkinsonia florida suffered the highest mortality, demonstrating no evidence of tradeoffs between bottomup and topdown factors. Interactions between host and larval density, and between host and number of eggs on seeds, showed variation between hosts in the mortality of beetles caused by competition and by parasitism, respectively. In addition, there was no evidence of egg size affecting parasitism of eggs. These results show the need of including in the traditional bottomup and topdown explanations, the study of factors that could be mediating their outcome such as the one examined here (competition). This need is more urgent now that we are exposing ecosystems to accelerated changes in structure, functioning, and composition.